Study about environmental naturally fungi infection in pet animals with experimental study - salman, Buraq shakir; S, Hashim M.; Jameel, Fadwa abdulrazaq; Yousif, Eman Hashim; Alrammah, Hanaa Salih Abd Ali; Aziz, Shahad Ehsaan; Ali, Musab Imad; Muhsin, Mueamar Natiq; Mahdi, Zahraa S.; Khan, Sikandar; Affiliation, Abdolmajid Ghasemian (Journal of Kerbala for Agricultural Sciences, 2024)
The current study was designed to investigate Environmental and natural fungi infection in pet animals and then experimentally to study fungi effects on tissues. Naturally infectious samples were fifty swabs in different pet animals (dogs, cats, rats, pigeons, and chickens) from the veterinary hospital of Eden Square in January 202. The findings were Cladosporum spp at (16%) ; Aspergillus flavus, Aspergillus niger at (14%); Rhizopus spp at (8%); Aspergillus ochraceus, Aspergillus terreus, and Penicillium chrysogenum at (6%); Chrysosporium spp, and Cryptococcus neoformans at (4%); Aspergillus fumigatus , Aspergillus ustus and Fusarium spp at (2%) in percentage with other unknown fungi. In doge, only 9 (9/50) samples of fungi, mainly Aspergillus flavus at (33.3%) with cladogram spp.at (22.3%). In cats, also 9 (9/50), mainly Penicillium spp at (22.25 %). In wild rats, fifty cotton swabs showed 12 (12/50) mainly Aspergillus niger, besides Rhizopus spp. At (25%). While in pigeons, only 10 (10/50), mainly Aspergillus niger, Cladosporum spp., and Cryptococcus neoformans at (20%). In chicken, only 5 (5/50), mainly Aspergillus ochraceus at (40%). Fifty albino mice aged 6-8 weeks and 25± 3gm body weight. They were separated in plastic cages and kept for adaptation at 2-3 weeks in the Animal House of the College of Veterinary Medicine, and they were fed standard pellets and water. These animals were divided into 5 groups containing 10 mice each: 1st one: control group treated with normal saline; 2nd Group infected with 0.1ml of Aspergillus flatus intraperitoneally; 3rd group infected with Aspergillus ochraceus 0.1ml intraperitoneally (IP); 4th group infected with 0.1ml Aspergillu niger IP; 5th group mice infected with Cryptococcus neoformans 0.1ml IP at single dose. After 3 weeks animals were scarified. Histopathological examination, in general, reports high incidences of necrotic lesions with granuloma and severe destructive changes, mainly in areas containing fungi hyphae that appear very clearly enclosed to necrotic and inflammatory foci, lung tissues suffering from prominent interstitial pneumonia with thick exudation, mainly fibrinous type. Liver tissues show massive necrosis with Kupfer cells and other inflammatory cell proliferation and evidence of apoptosis. Kidney samples appear with heavy degenerative changes ranging from swelling tubules to necrosis associated with severe inflammation caused by pyelonephritis and phlebitis. also, we saw fungi in the affected area. Spleen shows severe depletion and megakaryocyte proliferation and necrotic lesion. Fungi naturally infects occurs in pet animals and can transmitted to other animals in different environmental; area and can causes severe pathological lesions.